2010
DOI: 10.3390/rel2010001
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Spirituality, and Meaning Making: What Can We Learn from the Literature?

Abstract: Religion and spirituality are two methods of meaning making that impact a person's ability to cope, tolerate, and accept disease and pain. The biopsychosocialspiritual model includes the human spirit's drive toward meaning-making along with personality, mental health, age, sex, social relationships, and reactions to stress. In this review, studies focusing on religion's and spirituality's effect upon pain in relationship to physical and mental health, spiritual practices, and the placebo response are examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 73 publications
(77 reference statements)
0
16
0
1
Order By: Relevance
“…For example, Lison et al In their study showed that spirituality increases the resistance of individuals to pain. [20] Today, resilience in the areas of mental health has a special place and has been used for more than two decades as an important topic in theories and researches related to pregnancy health. [21] Resilience to the ability or the consequence of successful adaptation is defined by the threatening conditions that are associated with achieving a higher level of equilibrium and in threatening conditions.…”
mentioning
confidence: 99%
“…For example, Lison et al In their study showed that spirituality increases the resistance of individuals to pain. [20] Today, resilience in the areas of mental health has a special place and has been used for more than two decades as an important topic in theories and researches related to pregnancy health. [21] Resilience to the ability or the consequence of successful adaptation is defined by the threatening conditions that are associated with achieving a higher level of equilibrium and in threatening conditions.…”
mentioning
confidence: 99%
“…The American Society of Addiction Medicine's public policy statement defines addiction as a dysfunction …leading to characteristic biological, psychological, social, and spiritual manifestations (American Society of Addiction Medicine,, 2012). Extrapolating this definition of the impact of addiction to persons suffering from persistent pain corroborates adding the spiritual dimension into the biopsychosocial model for pain and SUD (Bussing, et al, 2009; Koenig, 2003; Lysne & Wacholtz, 2011; Sumalsy, 2002; Wacholtz, Pearce, & Koenig, 2007). …”
Section: A Comprehensive Approach To Persistent Pain and Addiction DImentioning
confidence: 55%
“…There are three overlapping components of the biopsychosocial model that have been well studied, and these are physical pain, psychological pain, and social/cultural pain (Altilio & Otis-Green, 2011; Grinstead, 2007; Keefe, Rumble, Scipio, Giordano, & Perri, 2004; Merskey & Bogduk, 1994; Merskey & Spear, 1967; Turk & Melzack, 2011). Examples of biopsychosocial indices include age, sex, ethnicity, mental health, personality, social relationships, stress reactions, and coping behaviors (Lysne & Wachholtz, 2011). …”
Section: A Comprehensive Approach To Persistent Pain and Addiction DImentioning
confidence: 99%
“…9,10,14 The psychospiritual process of meaning making can reduce stress on the body. Conversely, spiritual struggles increase physiological stress and promote increased morbidity and mortality.…”
Section: Multiple Dimensions Of Painmentioning
confidence: 99%